2011
DOI: 10.1111/j.1365-2362.2011.02633.x
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid microcarcinoma: clinicopathological characteristics and implications for treatment in 276 patients

Abstract: Patients presenting multifocal, bilateral PTMC with a maximum diameter > 5 mm and thyroid capsule invasion may have an increased risk of lymph node metastasis. These factors should be considered in the follow-up for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
6
37
0
2
Order By: Relevance
“…The multifocality increase the risk of LN metastasis. 35 In present study, CLN metastasis was found to be significantly high when there is multifocality (P=0.003) which detected in 80% of patients, in comparison to patients without multifocality CLN metastasis was detected in 55% of patients.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The multifocality increase the risk of LN metastasis. 35 In present study, CLN metastasis was found to be significantly high when there is multifocality (P=0.003) which detected in 80% of patients, in comparison to patients without multifocality CLN metastasis was detected in 55% of patients.…”
Section: Discussionmentioning
confidence: 77%
“…34 The presence of LN metastasis has been recorded to be 2-6 fold higher in patients with tumors of >4cm in comparison with smaller tumors. 35 In present study, CLN metastasis was more frequent in patients with tumor size >2cm and detected in 77% of patients, in comparison to patients with tumor size ≤2cm CLN metastasis was detected in 53% of patients (P=0.007). Multivariate logistic regression analysis revealed that tumor size >2cm was an independent predictor of CLN metastasis in patients with N0 PTC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In general, PTC has a good prognosis with a 5-year survival rate of 97-99% and 10-year survival rate of 98%. 1,9) Similarly, most PTMC have excellent prognosis. However, some studies have shown loco-regional recurrence, distant metastasis, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Papillary thyroid microcarcinoma (PTMC) is defined by the World Health Organization (WHO) as a PTC measuring ≤10 mm in the greatest dimension.…”
Section: Introductionmentioning
confidence: 99%